2018
DOI: 10.32404/rean.v5i4.1682
|View full text |Cite
|
Sign up to set email alerts
|

Teor E Fitoquímica De Óleo Essencial De Manjericão Em Diferentes Horários De Colheita

Abstract: O manjericão (Ocimum basilicum) é uma das plantas medicinais e aromáticas mais consumidas no mundo, sendo seu óleo essencial amplamente utilizado nas indústrias químicas, farmacêuticas e de flavorizantes. No entanto, muitos fatores podem influenciar no teor do óleo essencial, dentre eles o horário de colheita das plantas. Com vista nisso, o objetivo deste trabalho foi avaliar o teor e fitoquímica do óleo essencial em cultivares de manjericão submetidos a diferentes horários de colheita. O experimento foi condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
2
0
2
Order By: Relevance
“…As for the essential oil of basil, studies by Alves et al (2015) and Fattahi et al (2019) in pots with soil, Alcantara et al (2018) in the field, and Gondim Filho et al (2018) with the DFT hydroponic system in PVC tubes, found that the essential oil content of basil (Ocimum basilicum L.) did not exceed 1% using supply water for either irrigation or nutrient solution preparation. These values are lower than those recorded in the present study (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…As for the essential oil of basil, studies by Alves et al (2015) and Fattahi et al (2019) in pots with soil, Alcantara et al (2018) in the field, and Gondim Filho et al (2018) with the DFT hydroponic system in PVC tubes, found that the essential oil content of basil (Ocimum basilicum L.) did not exceed 1% using supply water for either irrigation or nutrient solution preparation. These values are lower than those recorded in the present study (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Essential oils are active principles activated by the secondary metabolism as a consequence of some stress suffered by the plant [14], common in crops in the conventional system. The biosynthesis of essential oils can be influenced by several factors, such as plant development stage and climatic factors related to temperature, humidity, precipitation, solar radiation and photoperiod [15], whereas the chemical composition of essential oils is determined by genetic factors, development stage, plant age and the interactions among the plant, microorganisms and insects [16]. Due to this diversity, it is important to know the content and composition of the essential oil of the basil variety worked.…”
Section: Introductionmentioning
confidence: 99%
“…O manjericão é uma das plantas medicinais e aromáticas mais consumidas no mundo, sendo seu óleo essencial amplamente utilizado nas indústrias químicas, farmacêuticas e de flavorizantes (ALCANTARA et al, 2018). Esta erva medicinal polivalente é conhecida por suas atividades antioxidante, antimicrobiana, anticâncer, antiinflamatória, antinociceptiva, antiúlcera, analgésica, cardiovascular, imunomoduladora, repelente e inseticida, entre outras (PANDEY et al, 2014).…”
Section: Introductionunclassified